2023
DOI: 10.1002/anie.202307690
|View full text |Cite
|
Sign up to set email alerts
|

Poly(Ethylene Piperidinium)s for Anion Exchange Membranes

Huanhuan Chen,
Ki‐Taek Bang,
Ye Tian
et al.

Abstract: The lack of anion exchange membranes (AEMs) that possess both high hydroxide conductivity and stable mechanical and chemical properties poses a major challenge to the development of high‐performance fuel cells. Improving one side of the balance between conductivity and stability usually means sacrificing the other. Herein, we used facile, high‐yield chemical reactions to design and synthesize a piperidinium polymer with a polyethylene backbone for AEM fuel cell applications. To improve the performance, we intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…7 Encouragingly, some significant progress has been achieved in terms of chemical stability and ionic conductivity of AEMs. 8,9 For example, AEMs based on the poly(norbornene) block copolymer showed <1.35% degradation after aging in 1 M NaOH at 80 °C for 1000 h; the OH − conductivity was as high as 201 mS cm −1 at 80 °C with a peak power density of 3.21 W cm −2 . 10 Particularly, the AEMs based on poly(aryl piperidine) (PAP) derivatives has shown both excellent alkaline stability (≥5000 h) and high ion conductivity (208 mS cm −1 @80 °C), as well as satisfied fuel cell performance (2.58 W cm −2 @80 °C at H 2 −O 2 ), in recent years.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Encouragingly, some significant progress has been achieved in terms of chemical stability and ionic conductivity of AEMs. 8,9 For example, AEMs based on the poly(norbornene) block copolymer showed <1.35% degradation after aging in 1 M NaOH at 80 °C for 1000 h; the OH − conductivity was as high as 201 mS cm −1 at 80 °C with a peak power density of 3.21 W cm −2 . 10 Particularly, the AEMs based on poly(aryl piperidine) (PAP) derivatives has shown both excellent alkaline stability (≥5000 h) and high ion conductivity (208 mS cm −1 @80 °C), as well as satisfied fuel cell performance (2.58 W cm −2 @80 °C at H 2 −O 2 ), in recent years.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The anion exchange membrane fuel cell (AEMFC) is an important technology for achieving renewable energy conversion and is receiving increasing attention for their potential commercial value. , Mainly due to the fast oxygen reduction reaction (ORR) kinetic, AEMFC allows for the use of nonprecious metals as catalysts, which significantly reduces the cost of the fuel cell. However, there are many challenges regarding the anion exchange membranes (AEMs), which is a key component of the AEMFC, such as low chemical and mechanical stability and insufficient ion conductivity . Encouragingly, some significant progress has been achieved in terms of chemical stability and ionic conductivity of AEMs. , For example, AEMs based on the poly­(norbornene) block copolymer showed <1.35% degradation after aging in 1 M NaOH at 80 °C for 1000 h; the OH – conductivity was as high as 201 mS cm –1 at 80 °C with a peak power density of 3.21 W cm –2 . Particularly, the AEMs based on poly­(aryl piperidine) (PAP) derivatives has shown both excellent alkaline stability (≥5000 h) and high ion conductivity (208 mS cm –1 @80 °C), as well as satisfied fuel cell performance (2.58 W cm –2 @80 °C at H 2 –O 2 ), in recent years. …”
Section: Introductionmentioning
confidence: 99%
“…4–6 Nevertheless, PEMFC advancement has not been devoid of challenges, particularly owing to the pervasive reliance on expensive platinum group metals (PGMs) as the eletrocatalysts. 5,7–10 In this context, anion exchange membrane fuel cells (AEMFCs) have attracted considerable attention as a promising alternative to their PEMFC counterparts. The rationale behind this burgeoning interest is rooted in the superior oxygen reduction kinetics and the cost-effectiveness of catalysts attributed to the high-pH working conditions within AEMFCs, which collectively position them as viable substitutes for PEMFCs.…”
Section: Introductionmentioning
confidence: 99%
“…9,23 Previous studies have shown that using aryl-ether free polymers and piperidinium-type cationic groups can effectively improve the performance of AEMs. 8,24 Bae et al demonstrated the synthesis of high molecular weight poly(biphenyl olefin) membranes with exceptional resistance to alkaline conditions. 25 Hu et al prepared poly(aryl piperidine) membranes, which showed no degradation even after prolonged immersion in 1 M KOH for 2000 hours.…”
Section: Introductionmentioning
confidence: 99%
“…Ion exchange membranes (IEMs) are key materials to an array of energy and environment-related technologies, such as H 2 /O 2 fuel cells, aqueous organic redox flow batteries (AORFBs), water electrolysis, osmotic energy-conversion devices, , ion-capture electrodialysis, etc. In these technologies, IEMs selectively transport specific ions and simultaneously act as electrical insulators.…”
mentioning
confidence: 99%